Improvement of investment attractiveness of Ukrainian financial instruments in the world market - Drannyk, Elina (Skhid, 2013)
The article identifies financial instruments of the international market, analyzes the financial institutions that operate internationally, identites the procedure ofUkraine’s integration to the financial market, proposes the ways to improve this mechanism.